Efektivitas Metode Jigsaw Terhadap Kegiatan Membaca dan Berhitung dalam Proses Pembelajaran Peserta Didik - Sirait, Fahruzi (SAFE-Network, 2023)
The background of this research was based on the findings regarding the low activity and mastery of students' concepts in reading and numeracy learning in class II SD IT Aroja Kisaran, Asahan Regency. SD IT Aroja Kisaran. The subjects in this study were 28 students of class II SD IT Aroja Kisaran, 2020-2021 academic year. The research method used was classroom action research which was carried out in two cycles. Each cycle consists of four stages, namely Planning, Implementation, Observation and Reflection. Data collection was carried out through tests, observation of student and teacher activities, interviews and documentation. Results: The results showed that: (1) The reasoning ability of students before learning to read had not yet reached completeness where the average score obtained only reached 72.67. (2) Students' reading reasoning ability after learning in cycle II has reached completeness where the average value obtained reaches 81.25. Meanwhile (3) the students' reasoning abilities before learning to count had not yet reached completeness where the average value obtained only reached 74.46. (2) and the students 'reading reasoning ability after learning in cycle II has reached completeness where the average value obtained reaches 80. The jigsaw type cooperative learning model is very effective in the reading and numeracy learning process to support the students' reasoning abilities